Targeted Radiotherapy: Microgray Doses and the Bystander Effect - Robert J. Mairs; Natasha E. Fullerton; Michael R. Zalutsky; Marie Boyd (SAGE Publishing, 2007)
Indirect effects may contribute to the efficacy of radiotherapy by sterilizing malignant cells that are not directly irradiated. However, little is known of the influence of indirect effects in targeted radionuclide treatment. We compared γ-radiation-induced bystander effects with those resulting from exposure to three radiohaloanalogues of meta -iodobenzylguanidine (MIBG): [ 131 I]MIBG (low linear energy transfer (LET) β-emitter), [ 123 I]MIBG (high LET Auger electron emitter), and meta -[ 211 At]astatobenzylguanidine ([ 211 At]MABG) (high LET α-emitter). Cells exposed to media from γ-irradiated cells exhibited a dose-dependent reduction in survival fraction at low dosage and a plateau in cell kill at > 2 Gy. Cells treated with media from [ 131 I]MIBG demonstrated a dose-response relationship with respect to clonogenic cell death and no annihilation of this effect at high radiopharmaceutical dosage. In contrast, cells receiving media from cultures treated with [ 211 At]MABG or [ 123 I]MIBG exhibited dose-dependent toxicity at low dose but elimination of cytotoxicity with increasing radiation dose (i.e. U-shaped survival curves). Therefore radionuclides emitting high LET radiation may elicit toxic or protective effects on neighboring untargeted cells at low and high dose respectively. We conclude that radiopharmaceutical-induced bystander effects may depend on LET and be distinct from those elicited by conventional radiotherapy.